Prevalence, Risk Factors, and Outcomes of Financial Stress in Survivors of Critical Illness - Khandelwal, Nita; Hough, Catherine L; Downey, Lois; Engelberg, Ruth A; Carson, Shannon S; White, Douglas B; Kahn, Jeremy M; Jones, Derek M; Key, Mary D; Reagan, Wen; Porter, Laura S; Curtis, J Randall; et al. (Critical care medicine, 2018)
Little is known about the experience of financial stress for patients who survive critical illness or their families. Our objective was to describe the prevalence of financial stress among critically ill patients and their families, identify clinical and demographic characteristics associated with this stress, and explore associations between financial stress and psychologic distress. Secondary analysis of a randomized trial comparing a coping skills training program and an education program for patients surviving acute respiratory failure and their families. Five geographically diverse hospitals. Patients (n = 175) and their family members (n = 85) completed surveys within 2 weeks of arrival home and 3 and 6 months after randomization. We used regression analyses to assess associations between patient and family characteristics at baseline and financial stress at 3 and 6 months. We used path models and mediation analyses to explore relationships between financial stress, symptoms of anxiety and depression, and global mental health. Serious financial stress was high at both time points and was highest at 6 months (42.5%) among patients and at 3 months (48.5%) among family members. Factors associated with financial stress included female sex, young children at home, and baseline financial discomfort. Experiencing financial stress had direct effects on symptoms of anxiety (β = 0.260; p < 0.001) and depression (β = 0.048; p = 0.048). Financial stress after critical illness is common and associated with symptoms of anxiety and depression. Our findings provide direction for potential interventions to reduce this stress and improve psychologic outcomes for patients and their families.